Randomized crossover trial of hand and hydrostatic casting for custom lower limb prosthetic sockets: Assessing socket comfort and fabrication time - Stefania Fatone; Amy Gravely; Andrea Giovanni Cutti; Andrew H. Hansen; Steven A. Gard (PLoS ONE, 2025)
The aim of this study was to compare diagnostic sockets made by hand casting and standing hydrostatic pressure casting in persons with lower limb amputation. This multi-site, single-masked, randomized crossover trial (ClinicalTrials.gov NCT04141748) involved a prosthetist at each site taking one cast by hand (H) and another using hydrostatic casting (S). The process of casting, rectifying and modifying a diagnostic socket was timed in minutes. Socket comfort score (SCS) was assessed during static fitting of the diagnostic socket before (initial) and after (final) any modifications were made by the prosthetist. Difference scores for comfort and timing were calculated for each pair of casts within prosthetist. Bootstrapping methods were used to determine if the mean difference scores were significantly different from zero. Eighty participants with unilateral lower limb amputation were enrolled, with 75 completing the study. The initial SCS was significantly better in the transfemoral amputation group (TFA, n = 24) for the socket made from hand casting (H: 7.1 ± 1.9, S: 6.5 ± 2.2; p = 0.043). The final SCS was significantly better in the transtibial amputation group (TTA, n = 51) for the socket made from hydrostatic casting (H: 7.5 ± 2.0, S: 8.1 ± 1.3; p = 0.025). Total fabrication time for hydrostatic casting was significantly greater than hand casting (H: 42.1 ± 15.6, S: 48.0 ± 10.7; p = 0.001). It took significantly more time to cast (H: 10.6 ± 5.5, S: 23.7 ± 6.1; p < 0.0001) and significantly less time to rectify with hydrostatic casting (H: 23.4 ± 11.1, S: 16.6 ± 17.2; p < 0.0001). There was no difference between casting approaches for time to modify the diagnostic socket (H: 8.1 ± 7.5, S: 7.7 ± 6.6; p = 0.641). In individuals with both TTA and TFA results suggest that hydrostatic casting took more total time than hand casting to fabricate a diagnostic socket. While hand casting resulted in a significantly more comfortable socket initially for the TFA group, hydrostatic casting led to a more comfortable final socket for the TTA group.